The predictive value of the shock index and modified shock index for the short-term mortality in patients with acute pulmonary embolism - Oz, Ahmet; Cinar, Tufan; Cagan Efe, Suleyman; Sait Altintas, Mehmet; Ayca, Burak; Karabag, Turgut (Annals of Medical Research, 2021)
Aim: The purpose of the study was to examine the relationship of shock index (SI) and modified shock index (MSI) with pulmonary embolism severity index (PESI) score in predicting short-term death in acute pulmonary embolism (APE) patients. Material and Methods: This retrospective analysis included 104 consecutive patients whose APE was confirmed using computerized tomographic pulmonary angiography. For each patient, the PESI score, the SI, and the MSI were calculated. The main endpoint of the study was short-term mortality.Results: Patients based on hemodynamic status or the PESI score upon admission were allocated into high risk and non-high risk groups. We noted that SI and MSI were significantly elevated in a high risk group (1.17 ± 0.17 vs. 0.77 ± 0.17 and 1.54 ± 0.29 vs. 1.05 ± 0.21, respectively, p 0.001). In a correlation analysis, we showed that SI and MSI were significantly correlated with the PESI score for short-term mortality (r = 0.491 and r = 0.504, respectively, p 0.001). An area under curve value of SI and MSI for short-term death were 0.66 (0.52-0.79 95% CI, p = 0.022) and 0.67 (0.53-0.80 95% CI, p = 0.026) respectively.Conclusion: The present study findings demonstrated that the SI and MSI may be applicable in predicting short-death in patients with APE.
Keywords: Acute pulmonary embolism; modified shock index; pulmonary embolism severity index score; shock index; short-term death